A process-based LCA for selection of low-impact DBPs control strategy for indoor swimming pool operation. (10th October 2020) - Rana, Anber; Dyck, Roberta; Hu, Guangji; Hewage, Kasun; Rodriguez, Manuel J.; Alam, M. Shahria; Sadiq, Rehan
Abstract: Disinfection by-products (DBPs) in public indoor swimming pools (ISP) are a major human health risk concern. Various DBPs control strategies have been developed as an integral part of ISP management; however, these strategies are associated with different energy and resource consumption and environmental impacts. In this study, a process-based life cycle assessment (P-LCA) framework is developed for determining the environmental impacts of DBPs control strategies in ISP management. The developed framework requires ISP operation information such as energy, water, and chemical use, and concentration data under each DBPs control strategy as inputs. The ReCipe2016 midpoint method is used to process the inputs and quantify the lifecycle impacts in terms of three categories: energy, water and chemicals. Based on the outputs, the best strategy is selected using the TOPSIS method. The developed framework is applied to an ISP located in Vancouver (Canada) to evaluate seven DBPs control strategies associated with various air circulation rates. The DBPs concentration data were sourced from a previous sampling campaign. The results show that energy use is the main contributor (87–94%) to the total environmental impacts as compared to chemical and water use (6–13%). Among the tested strategies, reduction of fan speed can yield maximum environmental benefits without compromising the DBPs control performance. On the other hand, supply of 100% fresh air at normal fan speeds results in higher environmental impacts compared to a baseline case despite the lower DBPs releases. The proposed P-LCA framework can facilitate pool operators in selecting low impact DBPs control strategies for sustainable ISP management. Highlights: Disinfection by-product control strategies were identified for indoor swimming pools. A process-based lifecycle assessment framework was proposed for the strategies. The developed framework was applied to an indoor swimming pool as a case study. The highest impacts are associated with energy use for pool heating and ventilation.